Giant omphalocele treated with simple daily dressing changes - Jayalaxmi shripati Aihole (Elsevier, 2022)
Omphalocele, also called exomphalos, is an anterior abdominal wall midline defect of variable size involving the umbilical ring containing the herniated viscera into a sac made up of peritoneum, amnion and Wharton's jelly. Giant omphalocele is an extreme version of this defect management of which is challenging. Author is reporting here a case of giant omphalocele managed initially by a simple yet novel conservative technique yielding subsequently good result.